PERANAN MRI ABDOMEN PADA KASUS HERLYN WERNER WUNDERLICH - Dessy Witrianti, Ratna; Iman, Nuzul; Serfina Fajarini, Eunike (JRI (Jurnal Radiografer Indonesia), 2020)
Background: Herlyn-Werner-Wunderlich syndrome (HWW) is a very rare genetic syndrome, a combination of anomalies between the mullerian and mesonephric ducts characterized by uterine didelphys, hemivaginal obstruction, and ipsilateral renal agenesis, also known as Obstructed Hemivaginal syndrome and Ipsilateral Renal Anomaly (OHVIRA). Magnetic Resonance Imaging (MRI) is an effective diagnostic support tool for finding out anatomical abdominal abnormalities with the right choice of protocol sequences to obtain optimal MRI images. Method: This study used a qualitative descriptive approach by presenting a case of a 20 year old female patient who had complaints of lower abdominal pain, no previous medical history and irregular menstruation. MRI Abdomen without contrast was performed using an MRI 1.5 Tesla signa explorer GE Healthcare at EMC Tangerang Hospital. Using the Coronal T2 SSFSE sequence, T1 fat sat LAVA, Axial T2 SSFSE, T1 fat sat LAVA breath hold method and Coronal 3D IFIR (MRA renal without contrast). Specifically for the pelvic area with the Axial T2 Propeller, Coronal T2 fat sat, and Sagittal T2 sequences. Result: In the Axial T2 propeller sequence, pelvic area retrieval revealed two separate uterine corpuses (uterus didelphys) accompanied by a heterogeneous oval lesion most likely originating from the left side of the vagina (hemivagina). Whereas in the Coronal T2 sequence the whole abdomen was taken and confirmed by the Coronal 3D IFIR, the right kidney was anatomically visible while the left kidney was not visible (agenesis). Conclusion: Abdominal MRI is a very accurate diagnostic tool to perform Herlyn-Werner-Wunderlich (HWW) syndrome without contrast agent with SSFSE T2 sequences, T2 propeller and 3D IFIR which have an important role in visualizing the quality of MRI images.